Urogenital Infection as a Factor of Development of Male Infertility - Melnyk, O.V.; Vorobets, M.Z.; Fafula, R.V.; Kovalenko, I.V.; Vorobets, Z.D.; Мельник, О.В.; Воробець, М.З.; Фафула, Р.В.; Коваленко, І.В.; Воробець, З.Д. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
To date, according to statistics, in Ukraine there is an increase in the number of infertile marriages. Many studies have emphasized the male factor of infertility Often, male infertility is the result of a previous infectious disease or an acute genital inflammation. Microorganisms that infect sperm usually persist in the urinary tract as a monoinfection or form associations. Microorganisms in biofilms are able to acquire new, not yet studied, properties. Persistence of pathogens in the urogenital tract of men triggers several mechanisms of the pathological action on sperm, the first of which is the infectious factor, directly related to the adhesion and resulting in a complete or partial decrease in the mobility and deformation of sperm. On the other hand, the development of the inflammatory process as a trigger of an immune response directed simultaneously against the infectious agent and the affected sperm. The increase in the number of leukocytes at the site of inflammation activates the secretion of biological substances which also have a damaging effect on sperm. The generalized data allow drawing a conclusion about the significant influence of opportunistic and pathogenic microorganisms as part of associations or monoinfection on the morphofunctional state of spermatozoa.